The impact of customer satisfaction on word-of-mouth: conventional banks of Malaysia investigated - Jan, Muhammad Tahir; Abdullah, Kalthom; Shafiq, Ali (2013)
Purpose – The main purpose of this paper is to test the impact of customer satisfaction on word-of-mouth in the banking industry of Malaysia.